Terapia através da dança com laringectomizados: relato de experiência - Peto, Ana Carla (2000)
This study describes the first contact of laringectomized people with dance in the Group of Support to Ostomized-Laringectomized Patients. This study aimed at searching for elements about the therapeutic and educative importance of dance to them. The technique utilized was group dynamics with the participation of twenty patients. Music and body movements were resources employed for the development of therapy through dance. Results showed a good involvement of the patients in the dynamics though verbal and non- verbal language as well as a decrease in stress.